Renal cell carcinoma metastases to the spermatic cord: review of the literature and case presentation. (November 2013) - Tran, M; Daly, P; Tran, T; Heathcote, P
We present a case of clear cell renal cell carcinoma with metachronous metastasis to the ipsilateral spermatic cord. We also review the literature of the rare instance of renal cell carcinoma metastasising to the spermatic cord.